Ulayat Land of Customary Law Communities Post Efforts to Administer Ulayat Land in Indonesia - Sariwati, Retno; Wisuda, Selvia; Rahayu, Dewi Ayu (Jurnal Cakrawala Hukum, 2023)
Failure to achieve the objectives of the law results in legal conflicts, in this case if there is a difference in treatment of customary law communities, it has the potential to result in the loss of customary law community customary rights over their customary forests, thus causing customary law communities to have difficulty in obtaining natural resources from the forest to meet their living needs. This study uses normative legal research using data collection techniques through literature studies and documents or archives. The results of this study are that the Regulation of the Minister of Agrarian Affairs has regulated the recognition of customary law communities and the granting of rights to customary law communities and customary institutions, the area where customary rights take place, the relationship, connection, and dependence of customary law communities with their areas, and the authority to regulate the use of land in their respective areas together. The public dimension of customary rights can be seen from the authority of customary law communities to regulate land/areas as their living space related to their use. How to cite item: Sariwati, Retno, Selvia Wisuda, and Dewi Ayu Rahayu. â€œUlayat Land of Customary Law Communities Post Efforts to Administer Ulayat Land in Indonesia.â€ Jurnal Cakrawala Hukum 14 no. 3 (2023): 333-345. DOI: 10.26905/idjch.v14i3.11278.